Requirement for CD4(+) T Cells in the Friend Murine Retrovirus Neutralizing Antibody Response: Evidence for Functional T Cells in Genetic Low-Recovery Mice - Super, Heidi J. (American Society for Microbiology, 1998)
Recovery from infection with the Friend murine leukemia retrovirus complex (FV) requires T-helper cells and cytotoxic T cells as well as neutralizing antibodies. Several host genes, including genes of the major histocompatibility complex (H-2) and an H-2-unlinked gene, Rfv-3, influence these FV-specific immune responses. (B10.A × A/Wy)F(1) mice, which have the H-2(a/a) Rfv-3(r/s) genotype, fail to mount a detectable FV-specific T-cell proliferative response but nevertheless produce FV-specific neutralizing immunoglobulin M (IgM) antibodies and can eliminate FV viremia. Thus, this IgM response, primarily influenced by the Rfv-3 gene, may be T-cell independent. To test this idea, mice were depleted of either CD4(+) or CD8(+) T-cell populations in vivo and were monitored for the effect on the neutralizing antibody response following FV infection. Surprisingly, mice in which CD4(+) cells were depleted showed undetectable FV-neutralizing antibody responses and high viremia levels compared to nondepleted or CD8-depleted animals. In addition to knocking out the FV antibody response, CD4(+) T-cell depletion reduced survival time significantly, further indicating the importance of CD4(+) T cells. These studies revealed the first evidence for a functional T-cell response following FV infection in these low-recovery mice and showed that CD4(+) T-helper cells are required for the Rfv-3-controlled FV antibody response.